EVALUATION IN BIBLICAL PROVERBS: A LINGUO-CULTURAL STUDY FROM A SYSTEMIC FUNCTIONAL PERSPECTIVE - Petrova, Roumyana; Stefanova, Diana (Proverbium - Yearbook, 2017)
The aim of this study is to examine more closely the realizations of evaluation in Biblical proverbs and to explain the role of evaluation in the construction of communities of shared values. The research method used in analyzing the corpus of 425 Biblical proverbs identified by Wolfgang Mieder is the appraisal analysis of J.R. Martin and P.R.R.White in combination with the culturematic analysis of R. Pe-trova. On the basis of the results obtained conclusions are drawn concerning the indexical and evaluative characteristics of the proverb cultureme. It is argued that the axiological charge proverbs get in actual use as a result of the inherent act of evaluation is an indispensable part of their meaning.